2020
DOI: 10.1021/acs.macromol.0c01366
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Poly(4-methyl-1-pentene): Efficient Catalytic Synthesis of a Transparent Cyclic Polymer

Abstract: Cyclic polymers possess properties that are significantly different from their linear analogs, such as higher densities, smaller hydrodynamic volumes, and higher glass transition temperatures. Poly­(4-methyl-1-pentene) (PMP), a linear polyolefin, is a commercial transparent thermoplastic and has applications in packaging materials and release membranes. Polymerizing 4-methyl-1-pentyne with a tungsten alkylidyne catalyst and subsequent hydrogenation (>99%) provided cyclic poly­(4-methyl-1-pentene) ( c-PMP). Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 80 publications
2
41
0
Order By: Relevance
“…This difference in time is due to the smaller hydrodynamic volumes that physically more compact cyclic polymers possess, which is consistently reported for cyclic polymers. 26,27 The R g and R h values and intrinsic viscosities of the cycles are also smaller than those of the linear samples of similar molecular weight and close to the theoretical expectation of g ≈ 0.66. 16,[28][29][30][31][32] Cyclic polymers are expected to have lower intrinsic viscosities than linear counterparts: theory suggests a ratio of g′ = [η cyclic ]/[η linear ] = 0.4-0.5.…”
Section: High-resolution Size Exclusion Chromatography (Sec)supporting
confidence: 75%
“…This difference in time is due to the smaller hydrodynamic volumes that physically more compact cyclic polymers possess, which is consistently reported for cyclic polymers. 26,27 The R g and R h values and intrinsic viscosities of the cycles are also smaller than those of the linear samples of similar molecular weight and close to the theoretical expectation of g ≈ 0.66. 16,[28][29][30][31][32] Cyclic polymers are expected to have lower intrinsic viscosities than linear counterparts: theory suggests a ratio of g′ = [η cyclic ]/[η linear ] = 0.4-0.5.…”
Section: High-resolution Size Exclusion Chromatography (Sec)supporting
confidence: 75%
“…Confirming a cyclic topology for cyclic polymers and producing them on a large scale is challenging. Though strong supporting evidence from size exclusion chromatography, dynamic light scattering, static light scattering, intrinsic viscosity, ozonolysis, and rheology clearly support a cyclic topology for polymers produced using our W-catalyst, ,, absolute evidence for the topology was missing. The AFM images presented herein for two different cyclic bottlebrushes and their size relationship with DP n , provide for the first time, absolute evidence for a cyclic topology.…”
Section: Discussionmentioning
confidence: 86%
“…To aid in comparing the cyclic architecture to a linear counterpart, linear PPA ( l -PPA ) was also synthesized using acetylacetonato­(1,5-cyclooctadiene) rhodium­(I) as the catalyst in THF at ambient temperature. , The resulting linear polymer was characterized by 1 H NMR spectroscopy (Figure S3) and GPC ( M n = 213 kDa and M w / M n = 1.68) (Figure S4). Evidence of the cyclic topology for the polymer prepared with the tungsten catalyst was obtained by two characteristic GPC plots. ,,,, When comparing the plot of log­(molar mass) versus elution time for c -PPA and l -PPA (Figure A), it was clear that at any point along the elugram that c -PPA eluted later than its linear counterpart of identical molecular weight. Moreover, the plot of log­(intrinsic viscosity) versus log­(molar mass) (Figure B) indicated a consistently lower intrinsic viscosity of c -PPA compared to its linear analog at a given molecular weight.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cyclic polyacetylene ( c -PA ) is now accessible from acetylene gas and catalyst 1 (Figure E), but the relationships between its cyclic topology and physical, electronic, and mechanical properties are unknown. Smaller hydrodynamic volumes, lower intrinsic and melt viscosities, and higher glass transition temperatures ( T g ) are properties that differ between linear and cyclic polymers. , Potentially more conjugated, and therefore more conductive, cyclic polymers have fewer degrees of freedom due to their inherent topological constraint . However, previous studies have suggested more limited conjugation lengths for cyclic polymers that could arise from segment bending/torsion, possibly mitigating cyclic topology effects on conductivity. , Nevertheless, attributable to a low-energy isomerization barrier for the ring structure, c -PA contains >99% trans double bonds.…”
Section: Introductionmentioning
confidence: 99%